2020
DOI: 10.3892/ol.2020.12163
|View full text |Cite
|
Sign up to set email alerts
|

Role of T cell immune response cDNA 7 on the pathology of acute graft‑versus‑host disease

Abstract: Activation of T lymphocytes is the initiating factor of the occurrence of acute graft-versus-host disease (aGVHD), and cytotoxic T lymphocyte antigen-4 (CTLA-4) is the inhibitory receptor for activating T cells. T cell immune response cDNA 7 (TIRC7) is considered an upstream regulator of CTLA-4; however, little is understood regarding the effects of TIRC7 on the regulation of CTLA-4 in aGVHD. The purpose of the present study was to evaluate the regulatory effects of TIRC7 on aGVHD, mainly in the pathology. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…In 2006, we demonstrated that TIRC7 colocalizes with CTLA-4 in human T cells and showed that the TIRC7-induced inhibitory effects on T cells are dependent on CTLA-4 expression, as a blockade of CTLA-4 completely abolished TIRC7-mediated effects [ 38 ]. A similar finding was reported on lymphocytes from patients with acute graft-versus-host disease by Zhu et al, who concluded that TIRC7 inhibits T cell activation by upregulation of CTLA-4 [ 39 ]. Given the breakthrough advancements achieved by inhibition of CTLA-4 in several advanced tumor entities and the evidence on its functional relation to TIRC7, TIRC7 should be considered a potential new upstream molecule to be addressed therapeutically in CCA and other solid tumors.…”
Section: Discussionsupporting
confidence: 83%
“…In 2006, we demonstrated that TIRC7 colocalizes with CTLA-4 in human T cells and showed that the TIRC7-induced inhibitory effects on T cells are dependent on CTLA-4 expression, as a blockade of CTLA-4 completely abolished TIRC7-mediated effects [ 38 ]. A similar finding was reported on lymphocytes from patients with acute graft-versus-host disease by Zhu et al, who concluded that TIRC7 inhibits T cell activation by upregulation of CTLA-4 [ 39 ]. Given the breakthrough advancements achieved by inhibition of CTLA-4 in several advanced tumor entities and the evidence on its functional relation to TIRC7, TIRC7 should be considered a potential new upstream molecule to be addressed therapeutically in CCA and other solid tumors.…”
Section: Discussionsupporting
confidence: 83%
“…TIRC7 appears to play a key role in graft versus host disease ( 16 ), allograft rejection ( 17 ) and autoimmune disorders ( 9 ). During solid organ transplant rejection, TIRC7 expression is increased in the allograft and decreased in peripheral blood lymphocytes ( 18 ).…”
Section: Introductionmentioning
confidence: 99%